2001
DOI: 10.1128/jcm.39.4.000-000.2001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Amantadine-Resistant Influenza A Viruses (H3N2) from Patients following Administration of Amantadine in Japan

Abstract: In Japan, the use of amantadine for treatment of influenza A virus infection was not accepted until November 1998, although it was widely used for treatment of Parkinsonism. Since then, we have monitored the emergence of amantadine-resistant viruses and isolated two viruses from patients on long-term treatment with amantadine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…However, it should be noted that chloroquine and hydroxychloroquine overdoses (although not common) do occur with a certain frequency and can result in significantly higher levels of drug (ϳ30 M) in the blood of these patients (19,22). Amantadine has been used as a therapy for influenza virus A infection (18,34). However, its use has diminished due to the fact that resistant strains emerge both in the laboratory and in patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that chloroquine and hydroxychloroquine overdoses (although not common) do occur with a certain frequency and can result in significantly higher levels of drug (ϳ30 M) in the blood of these patients (19,22). Amantadine has been used as a therapy for influenza virus A infection (18,34). However, its use has diminished due to the fact that resistant strains emerge both in the laboratory and in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The two classes of anti-influenza A virus compounds available currently are the ion channel blockers (amantadine or rimantadine) and the neuraminidase inhibitors (oseltamivir or zanamivir). It is well documented that amantadine-or rimantadine-resistant viruses are capable of causing disease and spreading person-to-person (Hayden and Hay, 1992;Iwahashi et al, 2001;Shiraishi et al, 2003). A recent study suggests that oseltamivir-resistant viruses can develop in humans, and patients harboring oseltamivir-resistant viruses can shed virus for significant amounts of time (Kiso et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several previous reports about the emergence of resistance to the anti-influenza adamantane (amantadane and rimantadine) drugs in seasonal human influenza A(H3N2) viruses, particularly from Japan where anti-influenza drugs are used widely [Iwahashi et al, 2001;Saito et al, 2002Saito et al, , 2003Saito et al, , 2006Saito et al, , 2007Suzuki et al, 2003;Kitahori et al, 2006;Yoneda et al, 2007], from the USA [Bright et al, 2006], and worldwide [Ziegler et al, 1999;Bright et al, 2005]. Bright et al found that out of 7000 influenza A isolates collected between 1994 and 2005, the frequency of adamantane resistance-associated mutations rose from 0.4% in 19940.4% in -19950.4% in to 12.3% in 20030.4% in -20040.4% in [Bright et al, 2005.…”
Section: Introductionmentioning
confidence: 99%